MODERN CONCEPTS OF SYSTEMIC ARTERIAL HYPERTENSION AS COMPLICATION OF BRONCHOPULMONARY DYSPLASIA - D Yu Ovsyannikov; A D Strutynskaya; M G Kantemirova; M A Karnaushkina (RUDN Journal of Medicine, 2017)
Arterial hypertension (AH) is highlighted as a complication of bronchopulmonary dys-plasia (BPD) in children. The review provides information on the incidence, pathophysiology, diagnosis and treatment of AH in children with BPD. After analyzing the studies, were identified risk factors for hypertension in children with BPD, the role of endothelial dysfunction in raising systemic blood pressure, analyzed therapy and consequences of AH in children with BPD.